Exploring the consequences of perceptions of the divine, and the church, in the making of self-identity: a case study of congregants from Roman Catholic and Charismatic communities in East London, South Africa - Sundberg, Dianne (Rhodes University, Faculty of Humanities, Department of Sociology, 2009)
This thesis explores the impact and consequences of the teachings of the church, perceptions of The Divine [God] and of Mary, in the making of personal identity. In spite of secularisation and the prediction that the church would collapse in the face of modern science, recent evidence suggests that - in its various forms - religion, and belief in a higher power remain important and potentially powerful aspects in society. A foundation stone of the Christian faith is the doctrine of Imago Dei: humanity created in the image of The Divine. Although not male, The Divine is repeatedly spoken of - and addressed - in anthropomorphic masculine terms, but perceived in gender-specific stereotypical terms. Alongside The Divine - in the Roman Catholic Church - is Mary, the mother of Jesus. She is spoken of in feminine terms, but is also perceived in gender-specific stereotypical terms. Although not officially considered to be divine, Mary fulfils important needs in the life of the believer and it is in this context that her influence is evaluated. The role of the church as a community - and social institution - is also explored, based on Giddens' theories of identity development. Belonging to a church community can provide a context for relationship, continuity, and trust. However, this potentially positive environment can have negative implications on self-identity in that restrictions on self-expression and personal choice can be as limiting as the sense of belonging is liberating. The patriarchal nature of the church is deemed to be of immense relevance. In order to establish the role of the church, The Divine, and Mary in the making of self-identity, in-depth interviews were conducted with twelve research participants belonging to Charismatic and Roman Catholic congregations, and Giddens' criteria for self-identity development was used as the standard for evaluating participants' personal sense of self-identity. Explored from the perspective of feminist theology, the findings of this qualitative research project suggest that it is more than gender language regarding The Divine that affects the agent's perception of The Divine, and that the role of the church in identity formation is not uniform in its influence. It also concludes that perceptions of Mary can be influential in the development of selfidentity.
Keywords: Giddens, Anthony; Catholic Church -- South Africa -- East London -- Case studies; Catholic Church -- Doctrines; Glory of God -- Case studies; Church -- South Africa -- East London -- Case studies; Feminist theology -- South Africa; Self -- Case studies; Identity (Psychology) -- Case studies